RUMINAL FERMENTATION AND BLOOD GLUCOSE AT LOW AND HIGH LEVEL INTAKE OF GROWING AND MATURE KACANG GOAT - Luthfi, N.; Lestari, C. M. S.; Purnomoadi, A. (Journal of the Indonesian Tropical Animal Agriculture, 2014)
This study was conducted to compare ruminal Volatile Fatty Acids (VFA) concentration andblood glucose in young and mature Kacang goats at different feeding levels. Eigth male young Kacanggoats weights at 12.75±2.68 kg (6-7 months) and male mature goat weights at ± 17.34±3.32 kg (8-12months) were used in this study. The pelleted complete feed was formulated to give 18,8% of CrudeProtein (CP) and 78.82% of total digestible nutrients (TDN). The experiment design was nested designexperimental 2x2 with 4 replications. The main factors (based on nested) were young and mature goatsand the second factor was low feeding (near maintenance level) and high feeding (2X maintenance).Data measured were daily feed intake, feed digestibilities, ruminal VFA concentration and bloodglucose. The data obtained were analyzed by using analysis of variance. The results showed that drymatter intake (DMI), digestible carbohydrates, digestible crude fiber, and digestible organic matter wasaffected by age (P<0.05), as well as level of feeding (P<0.001), but age and feeding level has no effecton digestibility (P>0.05). Ruminal VFA and blood glucose concentrations were found similar (P>0.05) neither in young and mature goats. However, VFA and concentration on the 3 and 6 h on high feeding aswell as blood glucose on 3 h in high feeding were higher than those on low feeding.